HQ : the hope quotient : measure it, raise it, you'll never be the same - Johnston, Ray, 1952- (Nashville, Tennessee : W Publishing Group, an imprint of Thomas Nelson, 2014)
Explains why hope is so important and offers to teach seven key factors that unleash hope and improve life circumstances.
Includes bibliographical references (pages 225-234).
Keywords: Hope -- Religious aspects -- Christianity; Conduct of life; Christian life; Nonfiction